Risk behaviors of high school students among parental separation families in urban society : (Case study conducted with Hanoi High School students) - Duong Thi Thu Huong (Technium Social Sciences Journal, 2020)
The study was conducted to explore the risk behaviors of high school students among parental separation families. The quantitative social survey was conducted in 2016 and 1333 Hanoi high school students were randomly selected and to be invited to do the survey. The result showed that there was 13% of all respondents were living in divorce or separated families. Noticeably, students from these families got a higher risk of different risk behaviors such as violent behaviors, suicide intention, and suicide attempts, tobacco smoking and shisha smoking, drug-using and the risk of having different unsafe traffic behaviors. For example, the proportion of high school students from divorce or separated families involved in tobacco or shisha smoking, drug-using, or involved in violent behaviors were about 1.5 times higher than these proportion among students living with both parents’ families. In terms of suicide intention and suicide attempt, about 24.4% students was living in separation families said that they ever had suicide intention and 8.8% of them reported that they ever had a suicide attempt, while these proportion among students living in both parents families were remarkable lower: 17.3% and 4.2% respectively. The implication of the study suggested some solutions for managing and supporting high school students among parental separated families which would be an increasing issue in urban society in Vietnam on the process of dynamic urbanization and industrialization.